A Blockchain-Enabled Architecture for Secure and Transparent Distribution of Disaster Relief Supplies - Karaduman, Ozgur; Gulhas, Gulsena (Mdpi, 2026)
Ensuring the reliable, auditable, and privacy-oriented distribution of donations in disaster logistics constitutes a critical challenge due to multi-stakeholder coordination difficulties and the risk of misuse. This study presents a modular architecture, named SecureRelief, operating on a permissioned Hyperledger Fabric platform. The architecture integrates authentication based on Self-Sovereign Identity (SSI), Decentralized Identifiers (DID), and WebAuthn, together with Attribute-Based Access Control (ABAC), and enables the verification of delivery evidence through privacy-preserving validation using zero-knowledge proofs (ZKP). Documents are stored off-chain on the InterPlanetary File System (IPFS), while only cryptographic summary (hash) values sufficient for integrity verification are maintained on-chain. In scenario-based laboratory experiments, the blockchain layer demonstrated low latency (p95 < 16 ms) and stable transaction throughput, confirming its scalability. While the API layer handled high burst request loads with a 0% error rate, the additional computational overhead introduced by the integrated privacy-preserving (ZKP) mechanisms kept the end-to-end transaction latency within acceptable limits for disaster management applications (3.5-4.5 s).
Keywords: disaster management; blockchain-enabled systems; Hyperledger Fabric; humanitarian relief logistics; SSI; ZKP; IPFS; multi-party attestation